Qalbu Therapy Through Talqin Dhikr Tharekat Qadiriyah Naqsabandiyah Suryalaya Sirnarasa Ciamis - Hasan Mud’is; Maulana Hasan Mud’is (Khazanah Sosial, 2022)
This study aims to determine the Islamic psychotherapy model of heart healing through the talqin dhikr approach at Pondok Pesantren Suryalaya Ciamis. This study uses a descriptive analytical method with a qualitative approach. To obtain complete data, data collection techniques such as direct observation, in-depth interviews, and literature study were used. The results of the study concluded that there are seven places where the human heart will have bad qualities, and that will be removed or treated by cleaning 7 places called latifah. The process of heart healing in the Tharekat Qodiriyah Naqsyabandiyah in Suryalaya, as taught by Sheikh Ahamd Shohibul Wafa Tajul 'Arifin, is to use two methods of dhikr, namely talqin dhikr jahar (hard) and talqin dhikr khafi (taste) method. The main purpose of the first jahar dhikr: to knock, wake the heart to avoid heart diseases that continue to reside in the human heart, Second: to close the devil's holes in humans and Third to destroy the human heart that has become stone